“Even the goats feel the heat:” gender, livestock rearing, rangeland cultivation, and climate change adaptation in Tunisia - Najjar, Dina; Baruah, Bipasha (Taylor & Francis, 2023)
Women's contributions to rangeland cultivation in Tunisia and the effects of climate change upon their livelihoods are both policy blind spots. To make women's contributions to rangeland cultivation visible and to provide policy inputs based on women's needs and priorities into the reforms currently being made in the pastoral code in Tunisia, we conducted fieldwork in three governorates. We conducted focus groups and interviews with 289 individuals. We found that men and women are negatively affected by rangeland degradation and water scarcity, but women are additionally disadvantaged by their inability to own land and access credit and by drought mitigation and rangeland rehabilitation training that only target men. Women are involved in livestock grazing and rearing activities to a greater extent than is assumed in policy circles but in different ways than the men from the same households and communities. Understanding how women use rangelands is a necessary first step to ensuring that they benefit from rangeland management. Women's growing involvement in livestock rearing and agricultural production must be supported with commensurate social and economic policy interventions. Providing all farmers with appropriate support to optimize rangeland use is particularly urgent in the context of resource degradation accelerated by climate change.